EBOLA - Tadeja Kotar (Zdravniški Vestnik, 2014)
The ongoing outbreak of Ebola virus disease is by far the largest in  the history of Ebola virus since its initial description in 1976. Apart from dramatic increase of detected cases in the current outbreak of Ebola virus disease in West Africa, there were also infections in Europe and USA. All three infections on western soil were in health workers, taking care of ill patients brought from West Africa. According to The World Health Organization  Ebola virus disease constitutes a public health emergency of international proportions, therefore we must be vigilant and prepared also in Slovenia.